Leg asymmetry and muscle function recovery after anterior cruciate ligament reconstruction in elite athletes: a pilot study on slower recovery of the dominant leg - Souissi, S.; Chaouachi, A.; Burnett, A.; Hue, O.; Bouhlel, E.; Chtara, M.; Chamari, K. (Biology of Sport, 2020)
The aim of this study was to examine performance in hopping tests in male athletes after anterior cruciate ligament reconstruction (ACLR) in the 4-to-6 months post-surgery period. A total of 36 athletes (24 ACLR and 12 controls) participated in this study. The ACLR group consisted of athletes who had undergone an ACLR on their dominant side (ACL DG n=16) or non-dominant side (ACL NDG n=8). Participants completed the following functional tests: a single-leg hop (SLH), single-leg triple hop (SL3H) and single-leg counter movement jump (SLCMJ), then the limb symmetry index (LSI) was calculated. There were no significant differences between the dominant and the non-dominant legs for all functional tests when comparing the ACL DG and the ACL NDG at 6 months after surgery. At 6 months after ACLR, the LSI of the two legs was within acceptable values, whether the athlete had the operation on their dominant or non-dominant leg (except the mean LSI for the ACL DG in the SLCMJ test). Furthermore, the control group showed higher performances as compared to the ACL group for all variables at 6 months after surgery, despite acceptable LSI. We concluded that an early return to "full participation to training" is not recommended in participants who have undergone an ACLR with patellar tendon grafts.